ANALISIS SENSORIS TERASI UDANG YANG DITAMBAHI BUBUK KULIT MANGGIS (Garnicia mangostana L) - Askur Rahman; Iffan Maflahah (Agroindustrial Technology, University of Trunojoyo Madura, 2016)
Shrimp paste is much-loved by the people. Terasi liked by the people of taste, smelland appearance. But shrimp paste have weaknesses pale white color display, so that sometimesthe manufacturer add harmful dyes such as rhodamine B. Whereas including rhodamine B dyethat is forbidden to be used for food coloring. Therefore, the necessary natural dye paste is safeto eat as mangosteen rind. The purpose of this study was to determine the nature sesnsoris inshrimp paste with the addition of mangosteen rind. The method used was a completelyrandomized design (CRD). Factors used is the concentration of mangosteen peel powder (0%,0.5%, 1%, 1.5% and 2%) to be added in the of paste. Parameters measured were sensori levelon the color, texture, flavor, aroma and overall. Research shows that added shrimp paste ofmangosteen peel powder were significantly different (p 0.05) in the level of preference ofcolor, flavor and overall, while the aroma and texture preference level not significantly different(p 0.05). Concentration of 2% powdered bark of the mangosteen is the treatment of the mostpreferred by the panelists.